Provider perspectives on contraceptive service delivery: findings from a qualitative study in Johannesburg, South Africa - Naomi Lince-Deroche; Cheryl Hendrickson; Aneesa Moolla; Sharon Kgowedi; Masangu Mulongo (BMC, 2020)
Abstract Background Healthcare providers' skills and attitudes are both barriers and facilitators of contraceptive uptake. In South Africa, migration of healthcare workers and the demands of the HIV epidemic have also contributed to inequitable access to sexual and reproductive health (SRH) care. Yet, the country has committed to achieving universal access to SRH services. We explored healthcare provider's opinions and attitudes on provision of contraceptive services in public facilities, their personal use of methods, and their thoughts on the recent integration of new contraceptive methods in their facilities. Methods We conducted a phenomenological, qualitative study in 2017 at an outpatient, public HIV treatment clinic and two primary healthcare clinics (PHCs) in Johannesburg, South Africa. We purposively selected providers who had worked at the facilities for at least six months and were seeing patients for HIV or SRH services. Trained study staff conducted semi-structured interviews. We conducted descriptive analyses for quantitative data, and used an iterative, thematic analysis approach for open-ended responses. Results We interviewed 14 healthcare providers (HIV clinic - 5; PHCs - 9). One respondent was a man; all were nurses. All respondents reported having ever personally used a contraceptive method; half (7/14) were currently using a method. Responses on service provision were conflicting. Respondents felt that their clinics currently met the contraceptive needs of their female patients through on-site services or referrals. However, they noted that staff shortages, lack of training, and a limited contraceptive offering meant that women did not always get the counselling or method they wanted. Respondents noted that the 'best' contraceptive methods for women were those that fit with a woman's lifestyle and medical needs; however, providers also felt strongly that injectables were best for all women. Recent introduction of the implant at one PHC and injectable contraceptives at the HIV clinic was not overly challenging, though there were concerns about staffing and demand creation for the new methods. Conclusions Respondents' conflicting responses revealed challenges with current service delivery, particularly contraceptive counselling. Addressing staff workloads and providing refresher training on contraception would contribute to increased contraceptive service capacity and quality in this setting.